-0.10(17)+0.40x=0.05(x-6)

Simple and best practice solution for -0.10(17)+0.40x=0.05(x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -0.10(17)+0.40x=0.05(x-6) equation:


Simplifying
-0.10(17) + 0.40x = 0.05(x + -6)

Multiply -0.10 * 17
-1.7 + 0.40x = 0.05(x + -6)

Reorder the terms:
-1.7 + 0.40x = 0.05(-6 + x)
-1.7 + 0.40x = (-6 * 0.05 + x * 0.05)
-1.7 + 0.40x = (-0.3 + 0.05x)

Solving
-1.7 + 0.40x = -0.3 + 0.05x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.05x' to each side of the equation.
-1.7 + 0.40x + -0.05x = -0.3 + 0.05x + -0.05x

Combine like terms: 0.40x + -0.05x = 0.35x
-1.7 + 0.35x = -0.3 + 0.05x + -0.05x

Combine like terms: 0.05x + -0.05x = 0.00
-1.7 + 0.35x = -0.3 + 0.00
-1.7 + 0.35x = -0.3

Add '1.7' to each side of the equation.
-1.7 + 1.7 + 0.35x = -0.3 + 1.7

Combine like terms: -1.7 + 1.7 = 0.0
0.0 + 0.35x = -0.3 + 1.7
0.35x = -0.3 + 1.7

Combine like terms: -0.3 + 1.7 = 1.4
0.35x = 1.4

Divide each side by '0.35'.
x = 4

Simplifying
x = 4

See similar equations:

| 3x+18=10x-59 | | 46+3y-19=12y-9-3y | | 0.11y+0.03(y+6000)=740 | | 1.2-(-0.5)=d | | p+16=2p-4+3p | | 9x+x=3x+44 | | X+2x+3x=46 | | 5t+1/2=t+5/4+t-3/4 | | 6(7-g)=12 | | 6(7-9)=12 | | y=1.2x+4 | | x-5/3+5/3=-x/5 | | -3r(4r-8)=-36 | | 40-8x=80-10x | | 2(r+1)=18+4r | | 3.5+2x= | | -11=-9+x/6 | | 2(3-g)=4 | | 4(120000-z)+10(120000-z)=1176000 | | 8x+7=-13 | | 3x/4+7/2=17 | | 46y=5(9y-7) | | 8x+6=12+6x | | -17y+3=-25 | | 2=3+m/10 | | 2x-5/11=4-x | | 8x-2=9x+6 | | (-3x^4yz^0)(4x^0y^4z)= | | 3.8x=2.9x+5.4 | | 8v+10=7v+5 | | -17+3=-25 | | 2f=-2f-20 |

Equations solver categories